PERFIL EPIDEMIOLÓGICO DE UMA POPULAÇÃO DE USUÁRIOS DE DROGAS DE ANÁPOLIS, GOIÁS - EPIDEMIOLOGICAL PROFILE OF A POPULATION OF DRUG USERS IN THE CITY OF ANÁPOLIS, GOIÁS - Priscilla De Paula Gusmão; Rayssa Ferreira Diniz Fernandes; Rhávila Cristina Rezende; Rodrigo De Souza Bonfim; Yuri Viktor Porto; Luciana Caetano Fernandes; Léa Resende Moura (UniEVANGÉLICA, 2017)
Objective: To describe the sociodemographic profile and the drug use pattern of rehabilitation centers in Anápolis and surroundings. Method: A cross-sectional, observational, descriptive and quantitative study. The research evaluated 144 drugs addicts in 7 centers from Anápolis and surroundings. The data was collected by objective and structured questionnaires elaborated by the researchers. The Chi-square test was used to verify the association among the categorical variables, and corrections by LikelihoodRatio. The significance level adopted was p<0,05. The software Statistical Package Social Science (SPSS, version 21) analyzed the data. Results: All patients were men, with an age average of 37,4 years old (DP ±11,6), 79 (54.9%) were unmarried from Goiás, and 67 (46.5%) whad brown skin with income Family ranging from 1 to 3 minimum wages. The main drugs used were alcohol (79,9%), followed by tobacco (64,4%) and cocaine/crack (57,6%). Fifteen patients (10,4%) had already injected drugs and most of them (60%) had already shared needles. Fourteen patients (9,7%) used 9 different kinds of drugs in the year before hospitalization. Conclusions: It was revealed the importance of outlining the sociodemographic profile and the pattern of drug use in order to establish public policies of prevention and treatment for this current public